Desenvolvimento sustentável corporativo: um estudo sobre práticas sustentáveis na indústria gaúcha de máquinas e implementos agrícolas - Azevedo, Juliana Birkan (2014)
Changes in global context, especially in environmental aspects, are increasing sustainability issues, which also encompasses the social and economic perspectives. In this context, the role of organizations as participants in society, generating profit and impacting on the environment, becomes clear in the triple helix of sustainability. Organizations have incorporated sustainability into their practices because they are agents with financial and technological resources, and therefore society expects these corporations to adopt sustainable practices (HINZ, VALENTINA AND FRANCO, 2006). There are many instruments that measure the sustainable development of organizations, however, there is a latent need for tools that measure sustainability in a complex way, which consider the three areas of sustainability: social, economic and environmental jointly. In this context the model developed by Chow and Chen (2011) becomes the ideal for measuring corporate sustainable development, since it includes 22 questions about sustainable practices in daily industries. Thus, this work, which has the general objective "check sustainable practices that are adopted in the agricultural machinery and implements sector of the State of Rio Grande do Sul that lead to Corporate Sustainable Development" used the model (CHOW AND CHEN, 2011) as support for the questionnaire survey instrument sent by electronic mail to the companies belonging to SIMERS. To this end, it was implemented a quantitative and descriptive research. Among the findings it was found that the economic, social and environmental variables, formed by practices arising from Chow and Chen (2011) model positively influence the Corporate Sustainable Development, confirming the three hypotheses of the research. The results also showed that social variable is the one that most influences the Corporate Sustainable Development in the studied organizations, which depends 28.8% of the social variable, 11.3% of the economic variable and 17.6% of the environmental variable. In addition, open questions were added about the practices that are performed and that are intended to be adopted by organizations, as it was noticed a dominance of quotes regarding environmental practices.